Peran Pendamping Kasus Perempuan Korban Kekerasan (KDRT) di UPTDPPA Tangerang Selatan - Muhammad Ardiansyah Yulianto; Wa Ode Asmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
The role of assistance includes actions and interactions that occur in victims of domestic violence (KDRT) who are in the institution. This study aims to determine how the role of the assistant provides assistance. This field research uses Qualitative research, the informant selection technique uses the Proposive Sampling Technique. And data collection is obtained from the results of interviews, observations, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The location of this study is at the Regional Technical Implementation Unit Institution for the Integrated Service Center for the Empowerment of Women and Children. Jalan Rawa Buntu NO.18 RT.03 RW.02 Kelurahan Rawa Buntu, Serpong District, South Tangerang City. The results of the study show that UPTDPPA South Tangerang provides assistance to victims of domestic violence by focusing on case assistance from the initial stage to the final stage, with the main goal of recovering and strengthening victims. The assistance mechanism is completed with case management involving partnerships with mediators, psychologists, and legal experts to provide comprehensive services. Although there are inhibiting factors such as the lack of client openness in explaining the problems faced. Meanwhile, the supporting factors are the existence of a team of experts, including counselors, lawyers, social workers, and medical personnel. The conclusion in this study shows that UPTDPPA is effective in providing support to victims of domestic violence. The existence of a team of experts with in-depth knowledge, including counselors, lawyers, social workers, and medical personnel, is the main supporting factor. This supporting factor ensures the provision of appropriate and necessary assistance for victims of domestic violence at UPTDPPA.